ZnO/graphene-oxide nanocomposite with remarkably enhanced visible-light-driven photocatalytic performance - Li, Benxia; Liu, Tongxuan; Wang, Yanfen; Wang, Zhoufeng (Journal of colloid and interface science, 2012)
[Display omitted] ► ZnO/graphene-oxide (ZnO/GO) nanocomposite was synthesized via a facile chemical deposition route. ► The ZnO/GO nanocomposite exhibited remarkably enhanced visible-light-driven photocatalytic performance. ► The mechanism for photocatalytic degradation of methylene blue (MB) under visible light was discussed. In this work, a high-performance photocatalyst of ZnO/graphene-oxide (ZnO/GO) nanocomposite was synthesized via a facile chemical deposition route and used for the photodegradation of organic dye from water under visible light. The nanocomposite was characterized by X-ray diffraction, X-ray photoelectron spectroscopy, scanning electron microscopy, transmission electron microscopy, Brunauer–Emmett–Teller N2 adsorption–desorption analysis, and UV–Vis diffusion reflectance spectroscopy. The ZnO/GO nanocomposite consisting of flower-like ZnO nanoparticles anchored on graphene-oxide sheets has a high surface area and hierarchical porosity, which is benefit to the adsorption and mass transfer of dye and oxygen species. For the photodegradation of organic dyes under visible light, ZnO/GO nanocomposite exhibited remarkably enhanced photocatalytic efficiency than graphene-oxide sheets and flower-like ZnO particles. Moreover, the photocatalytic efficiency of ZnO/GO nanocomposite could be further improved by annealing the product in N2 atmosphere. The outstanding photocatalytic performance was ascribed to the efficient photosensitized electron injection and repressed charge carriers recombination in the composite with GO as electron collector and transporter, thus leading to continuous generation of reactive oxygen species for the degradation of methylene blue.